Buprenorphine Implant Removal 7 Years Postinsertion: A Case Report. Issue 1 (January 2019) - Frost, Michael; Bobb, Raymond
Abstract : N/A: A long-acting buprenorphine subdermal implant, Probuphine, was approved by the Food and Drug Administration (FDA) in May 2016, for the maintenance treatment of patients with opioid-use disorder. Long-acting implants offer the potential benefits of improved medication adherence, consistent daily dosing, and reduced risk of medication diversion. Sets of 4 implants are typically inserted for a period of 6 months and then removed. Similar technology has been successfully utilized in implantable formulations of birth control medications; however, there is currently little clinical experience involving buprenorphine implants that have remained in the body for extended periods of time. This is a case report involving an early clinical study subject who had been lost to follow-up at the time of the original study because of incarceration. Despite the protracted duration of time since initial implantation, all 4 implants remained easily palpable, and displayed little physical deterioration or tissue infiltration. All implants were able to be removed using the standard explant technique of midline incision and limited tissue dissection. While extending length of treatment beyond the indicated 6-month period is not being espoused, this case demonstrates that although situations may arise where implants may remain in an individual for longer than the intended dosing period, implants may be removed safely despite remaining implanted for longer than intended.